A Study on the Role of Transaction Monitoring in the Detection and Prevention of Cryptocurrency Fraud and Money Laundering: Implications for Fraud Monitoring Professionals - Helou, George Antoine (Digital Repository of Theses - SSBM Geneva, 2024)
Given the anonymity and unregulated nature of financial transactions, money laundering and cryptocurrency fraud are a growing problem in the financial industry. Numerous studies have acknowledged this fact and advocated a complex socio-technical approach to improve the understanding of cryptocurrency-related crimes and risk assessment. However, the proliferation of cryptocurrencies has made it more difficult to combat these crimes. As most virtual currencies and other digital assets offer pseudo anonymity and operate in a decentralised manner, the effectiveness of tools and techniques to detect and prevent money laundering and cryptocurrency fraud has also been questioned. Therefore, this study assesses the effectiveness of rule-based and behaviour-based transaction monitoring tools, emphasises the importance of cooperation between financial institutions and regulators, highlights the fundamental differences between traditional and modern fraud detection tools, and offers recommendations for fraud monitoring professionals. The study uses a mixed methods approach, collecting qualitative data from eleven secondary sources and quantitative data through questionnaires distributed to twelve participants. The results of the study vi show that while rule-based monitoring is essential for national regulators, over-reliance on this method leads to low fraud detection and high false positive rates. On the other hand, behaviour-based monitoring techniques were more effective and improved detection rates due to their low false positive rate. The study found that cooperation and collaboration between crypto developers, financial institutions and regulators is crucial to foster innovation and ensure the safety of investors and other stakeholders. In addition, the study found that traditional tools to prevent money laundering and fraud related to cryptocurrencies are insufficient, whereas modern tools such as graph methodology are effective in detecting criminal patterns and fraudulent transactions. It has therefore been suggested that the banking and financial sector adopt a multi-layered approach to transaction monitoring that includes a combination of traditional and modern tools, as well as rule-based and behaviour-based monitoring methods.